Impediments to knowledge sharing in the interpersonal relationships of business consultants - Sniazhko, Sniazhana (My University, 2011)
Knowledge sharing at different organizational levels is a fundamental aspect of companies' operation today. This research focuses on knowledge sharing process at the interpersonal level of individuals. Since knowledge sharing is a critical point of successful operation of consulting companies in particular, the study investigates knowledge sharing in the interpersonal relationships of consultants. The research addresses two main research questions. The first research question investigates characteristics of the interpersonal relationships that have influence on knowledge sharing. The second research question looks at the impediments to knowledge sharing in the interpersonal relationship of consultants. It also examined the extent of impediments' significance across cultures, particularly Lithuania and Finland. The empirical study was conducted through qualitative research method by means of semi-structured interviews. 13 semi-structured interviews were carried out to investigate the research questions, eight of the interviewees were organized with Lithuanian consultants and five with Finnish consultants. Social capital theory and interpersonal similarity were found to be aiding tools in understanding the behavior of individuals in knowledge sharing processes at the interpersonal level. Dimensions of social capital theory and characteristics of interpersonal similarity were expressed in different forms and, correspondently, these forms render different levels of significance in knowledge sharing. Certain impediments to knowledge sharing were observed in the interpersonal relationships. Particularly, lack of shared cognitive ground and lack of trust, which was expressed in different patterns, were the most frequently repeated barriers to knowledge sharing in different cultural settings.
Keywords: Knowledge Sharing; Knowledge Sharing Barriers; Interpersonal Relationships; Interpersonal Similarity; Social Capital Theory; Consulting Companies; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|